Exercise and Its Effects on Gestational Diabetes Mellitus and Related Parameters - Sheema Yousuf; Majida Zafar; Arfa Tabassum; Batool SyedaMazhar (ziauddin University, 2020)
Background: Gestational Diabetes Mellitus (GDM) has now become one of the most common and important complication of pregnancy worldwide. There are conflicting results of various studies regarding the role of exercise in reducing the risk of GDM. Therefore, the aim of this study was to determine the effectiveness of exercise on prevention of gestational diabetes. Methods: It is a randomized controlled study directed in the obstetrics and gynecology outpatient clinic of Pakistan Institute of Medical Sciences (PIMS) hospital Islamabad beginning from 6 June 2016 to 5 December 2016 including 170 pregnant women satisfying the inclusion criteria. Group A received routine antenatal care while Group B included the pregnant women that were advised brisk walk for 30 minutes three days per week. At 24-28 week of pregnancy, 75gm oral glucose tolerance test (OGTT) was performed and International association for Diabetes in Pregnancy Study Group (IADPSG) and Hyperglycemia and adverse pregnancy outcome (HAPO) standards, determined GDM. Chi Square was applied for comparing GDM frequency and p-value ≤0.05 was considered as significant. Results: The mean age of the patients was 28.08 ± 4.15 years and mean gestation of pregnancy was 17.18 ± 0.78 weeks. Gestational diabetes was seen in 08 (9.41%) patients of non-exercising group while in exercise group only 01 (1.18%) patient had GDM (p-value 0.016). Conclusion: Moderate exercise during pregnancy decreases the risk of gestational diabetes mellitus and is safe for the mother and the baby. However, more studies are needed to establish recommendations.